Numerical study on the optimized thickness of layer configuration against the 7.62 APM2 projectile - Morghode, Divyanshu S.; Thakur, D. G.; Salunkhe, Sachin; Cepova, Lenka; Abouel Nasr, Emad (Frontiers in Mechanical Engineering, 2024)
This study aimed to select suitable materials and optimize the thickness of these materials such that they can prevent the perforation of 7.62 mm AP bullets at 830 m/s impact velocity. A numerical method is used to analyze the impact on layered configurations of Al2O3 and Al 7075-T651 to fulfill this aim. In order to optimize the thickness of the armor, normal impact and angular impact conditions were considered. Initially, a 20 mm Al2O3 front plate with a 20 mm Al 7075-T651 back plate is analyzed for layered configuration. Backplate thickness is reduced in steps to 10 mm such that no plastic deformation is observed on the rear side of the target. For further optimization of weight, the thickness of the Al2O3 plate is reduced to 18 mm. The weight of this configuration is 1.77 Kg, and the areal density is 97.22 kg/m2. This configuration is analyzed for target orientations such as 80°, 70° and 60°. In the present analysis, the projectile deformed in a mushroom shape for 90° and 80° target orientations, while for 70° and 60° target orientations, the projectile experienced more damage on the shank part.The most effective configuration with the highest degree of ballistic performance is a layered combination of 18 mm Al2O3 front plate and 10 mm Al 7075-T651 back plate at 70° target orientation.